2017
DOI: 10.4269/ajtmh.16-1006
|View full text |Cite
|
Sign up to set email alerts
|

Use of Serologic Responses against Enteropathogens to Assess the Impact of a Point-of-Use Water Filter: A Randomized Controlled Trial in Western Province, Rwanda

Abstract: Diarrhea is a leading contributor to childhood morbidity and mortality in sub-Saharan Africa. Given the challenge of blinding most water, sanitation, and hygiene (WASH) interventions, diarrheal disease outcome measures in WASH intervention trials are subject to potential bias and misclassification. Using the platform of a cluster-randomized controlled trial of a household-based drinking water filter in western province, Rwanda, we assessed the impact of the drinking water filter on enteric seroconversion in yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Given the irregular interannual occurrence of cholera in Zanzibar and the heterogeneity in the geography of each outbreak, providing quantitative estimates of the impact of ZACCEP will be challenging, without careful thought. Key indicators for measuring progress could include the distribution of times between outbreaks, the proportion of the population infected by cholera (but not necessarily symptomatic, eg, [ 17 ]), and changes in RR within shehias regularly affected by cholera.…”
Section: Discussionmentioning
confidence: 99%
“…Given the irregular interannual occurrence of cholera in Zanzibar and the heterogeneity in the geography of each outbreak, providing quantitative estimates of the impact of ZACCEP will be challenging, without careful thought. Key indicators for measuring progress could include the distribution of times between outbreaks, the proportion of the population infected by cholera (but not necessarily symptomatic, eg, [ 17 ]), and changes in RR within shehias regularly affected by cholera.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, children living in environments contaminated with feces have a higher risk of acquiring intestinal protozoan infections. There is limited and mixed evidence assessing the effect of combined water, sanitation, and handwashing (WSH), or nutritional interventions on protozoan infections: 2 trials with limited statistical power reported no effect of water treatment on Cryptosporidium or Giardia [ 7 , 8 ], 1 water treatment trial reported a reduction in Cryptosporidium [ 9 ], 1 sanitation trial reported a reduction in Giardia [ 10 ], and exclusive breastfeeding and improved nutritional status potentially confer immunity against protozoan infections [ 11–13 ].…”
mentioning
confidence: 99%
“…Recombinant Campylobacter p18 and p39 antigens [60][61][62] were expressed and purified as previously described [17] . E. histolytica LecA antigen [14,63,64] was kindly provided by William Petri (University of Virginia) and Joel Herbein (TechLab).…”
Section: Multiplex Bead Assaysmentioning
confidence: 99%
“…The β subunit protein from cholera toxin was purchased from Sigma Chemical. The GST negative control protein (15 μg), Cryptosporidium Cp17 (6.8 μg) and Cp23 (12.5 μg) proteins and the Campylobacter p39 protein (25 μg) were coupled to 1.25 x 10 7 beads using the indicated protein amounts [17] . The Giardia , E. histolytica , ETEC, cholera, and Campylobacter p18 proteins were coupled using 30 μg of protein per 1.25 x 10 7 beads.…”
Section: Kenyamentioning
confidence: 99%
See 1 more Smart Citation